Are there spillover effects from Hong Kong and the United States to Chinese stock markets - Katharina Diekmann (Osnabrück University, Institute of Empirical Economic Research, 2011)
Stock market integration of mainland China is analyzed before and after the liberalization of Chinese stock exchange segments. We apply a causalityin-variance procedure, using four mainland China stock market indices, two indices of the stock exchange in Hong Kong and the Dow Jones Industrial index. We find evidence of global and regional integration, but we do not find evidence for increasing integration after stock market liberalization, neither with Hong Kong nor with the United States.
Keywords: C23; G10; G15; 330; Chinese stock market integration; spillover effects; causality-in-variance